Symptomatic Severe Stenosis of Cavernous Internal Carotid Artery Stenting: A Case Report with Short Literature Review - Karki, Mohan; Rajpal, Girish (Asian Journal of Neurosurgery, 2024)
Intracranial internal carotid artery (ICA) stenosis is rarely reported as compared with extracranial ICA stenosis. Atherosclerosis is one of the major beginnings of stenosis of vasculatures, which may lead to ischemic stroke causing morbidity and mortality. We report the case of a 60 -year-old man presented to us with complaints of multiple episodes of dizziness, mild headache, and transient left arm weakness for 3 months and had history of smoking, hypercholesterolemia (high level of low-density lipoprotein level = 220 mg/dL), diabetes mellitus, and hypertension under medication. No neurological deficits were observed at the time of admission. Patient underwent angioplasty and stenting with drug-eluting balloon-expandable coronary stent. Patient was discharged well at the 3rd day of procedure. No recurrence of stroke and restenosis were noted till 3 months of follow-up period. Stenting following angioplasty for treatment of symptomatic severe cavernous ICA stenosis with everolimus-eluting coronary balloon-expandable stent, Xience Xpedition, is safe and effective.
Keywords: cavernous internal carotid artery; severe stenosis; angioplasty; everolimus-eluting coronary stent; outcome